208k views
4 votes
3 + 2-(-3)-7=
Please add step by step and make sure the answer is correct

2 Answers

6 votes

Answer:

3 + 2-(-3)-7=1

Explanation:

The answer is 1

User Findall
by
4.9k points
4 votes

Answer:

1

Explanation:

1.First you have to multiply the negative to the parenthesis(Pemdas)

2.add 3+2=5

3.add 5+3=8

4.subtract 8-7

3+2-(-3)-7=

3+2+3-7=

5+3-7=

8-7=

=1

User Gunderson
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.